Highly Photoluminescent Monolayer MoS2 and WS2 Achieved via Superacid Assisted Vacancy Reparation and Doping Strategy - Feng, Qiushi; Sun, Ying; Li, Yuanzheng; Yan, Jiaxu; Zhong, Weiheng; Yang, Guochun; Liu, Weizhen; Xu, Haiyang; Liu, Yichun (Laser & photonics reviews, 2021)
Chemical treatment of transition‐metal dichalcogenides (TMDs) by organic superacid bis(trifluoromethane) sulfonamide TFSI, has been proved as an effective route to reduce the density of sulfur vacancies and improve photoluminescence quantum yield (PL QY) of monolayer TMDs (1L‐TMDs). However, such kind of functional organic superacid is only limited to the TFSI so far, and the underlying mechanism of PL enhancement remains elusive. Here, a novel organic superacid trifluoromethanesulfonic (TFMS), which can significantly increase the PL QYs of 1L‐MoS2 and 1L‐WS2 to 14.1% and 56.7% respectively, the relatively higher PL QY values for chemical vapor deposition grown 1L‐TMDs is explored. Through in‐depth study and analysis with scanning transmission electron microscopy and density functional theory calculation, PL enhancement mechanism is attributed to a synergistic effect of TFMS‐induced p‐type doping and sulfur vacancy reparation. Especially, the respective function of [CF3SO3]− and H+ of TFMS played in superacid‐induced PL enhancement is clearly identified. The results not only enrich the functional superacid family that can remarkably improve the luminescence performance of TMDs, but also clearly reveal the PL enhancement mechanism of superacid‐treated TMDs. A novel organic superacid trifluoromethanesulfonic (TFMS) is explored to significantly improve the photoluminescence quantum yield of chemical vapor deposition‐grown monolayer MoS2 and WS2 to 14.1% and 56.7%, respectively. Through in‐depth study and analysis with scanning transmission electron microscopy and density functional theory calculation, luminescence enhancement mechanism is attributed to a synergistic effect of TFMS‐assisted sulfur vacancy reparation and p‐type doping.